FUNGSI DAN TUGAS OTORITAS JASA KEUANGAN BERDASARKAN UNDANG-UNDANG NOMOR 21 TAHUN 2011 TENTANG OTORITAS JASA KEUANGAN - ABIDIN YUNUS; BISMAR NASUTION; MAHMUL SIREGAR (TRANSPARENCY, 2013)
Before the establishment of Otoritas Jasa Keuangan (OJK), banks are regulated and supervised by Bank Indonesia (BI), while the non-bank financial companies regulated and supervised by Badan Pengawas Pasar Modal-Lembaga Keuangan (Bapepam-LK). But after the crisis hit in 1998, it gives birth to the idea of establishing an independent oversight agency. However, this agency is formed after a long process of waiting. Exactly after the issuance of Undang-Undang No. 21 Tahun 2011 tentang Otoritas Jasa Keuangan. The issues that will be raised by the author is how OJK regulated in Indonesia, how is the position of financial services authority in other countries, what is the functions and duties of OJK. The research method used by the author was a literature research, which is the juridical normative that aims to describe in a systematic, factual and accurate to state the object of a study by research based on normative legal provision. Research source used is sourced from secondary data. Otoritas Jasa Keuangan is an independent body in carrying out its duties and powers under Undang-Undang No. 21 Tahun 2011 tentang Otoritas Jasa Keuangan. In the UK, Financial Services Authority headed by a chairman. But in carrying out day-to-day operational activities carried out by a CEO. In Japan, Financial Services Authority headed by the commissioner in charge of administrative law judge, planning and coordination bureau, inspection bureau, and supervisory bureau. General functions and tasks of OJK is to regulate and supervise the activities of financial services in banking, capital markets, and other financial institutions. In the banking sector, the functions and duties related to OJK were only microprudential aspects such as institutional, business activities, and assessment of banks’ health. In the sector of the capital markets and other financial institutions, OJK carry out all the duties and authority vested in Bapepam-LK, ie foster, organize, and oversee the day-to-day activities of the capital markets and to formulate and implement the policies and technical standardization in the field of financial institutions. Kata Kunci: Fungsi, Tugas, Otoritas Jasa Keuangan